Modeling coordination between renewables and grid: Policies to mitigate distribution grid constraints using residential PV-battery systems - Paul Neetzow; Roman Mendelevitch; Sauleh Siddiqui (Deutsches Institut für Wirtschaftsforschung (DIW), 2018)
Distributed photo-voltaic (PV) generation is one of the pillars of energy transitions around the world, but its deployment in the distribution grid requires costly reinforcements and expansions. Prosumage - consisting of a household-level PV unit coupled with a battery storage system - has been proposed as an effective means to facilitate the integration of renewable energy sources and reduce distribution grid stress. However, tapping its full potential requires regulatory interventions; otherwise, system costs could rise despite increasing flexibility. We analyze the effectiveness of different policy schemes to mitigate the need for distribution capacity expansion by incentivizing beneficial storage operation. Our novel top-down modeling approach allows analyzing effects on market prices, storage dispatch, induced distribution grid requirements, system costs, and distributional implications. Numerical results for German power system data indicate that required distribution grid requirements can be reduced through simple feed-in policies. A uniform limit on maximum grid feed-in can leave distribution system operators better off, even if they fully compensate prosumage households for foregone revenue. Policies imposing more differentiated limits at the regional level result in only marginal efficiency improvements. Complete self-sufficiency (autarky) is socially undesirable, as it confines important balancing potential and can increase system costs despite adding storage.
Keywords: C61; L94; Q41; Q42; 330; residential storage; renewable integration; distribution system operator; prosumage; policy; multi-level games; MPEC